Multimorbidity as a predictor of mortality in companion dogs - Eric R. Foreman; Laura Corlin; Kate E. Creevy; Jessica M. Hoffman; Joshua M. Akey; Rozalyn M. Anderson; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Matthew D. Dunbar; Virginia R. Fajt; Erica C Jonlin; et al. (GeroScience, 2026)

Higher burden of neuropsychiatric symptom-like behaviors associated with canine cognitive dysfunction compared to normal aging in the Dog Aging Project - Daniel W. Fisher; Jillian R. Fisher; Silvan R. Urfer; NhiVan A. Tran; Kathleen F. Kerr; Martin Darvas (GeroScience, 2026)

Downstream water quality impacts persist despite mountaintop coal mine reclamation in the Canadian Rocky Mountains - Colin A. Cooke; Craig A. Emmerton; William F. Donahue; Jason G. Kerr (Environmental Pollution, 2025)

An enhanced aquifer vulnerability index applied to a mixed agricultural-urban county in Iowa, USA - Keith E. Schilling; Calvin F. Wolter; Phil Kerr; Stephanie Tassier-Surine; Joseph Honings (Hydrogeology Journal, 2025)
Vulnerability assessments are frequently used to guide land use and resource planning efforts in groundwater-dependent regions. However, many readily available methodologies are not particularly useful to assess pollution risks to aquifers in specific hydrogeologic settings. In this study, aquifer vulnerability was evaluated in Black Hawk County, Iowa (USA), using an index-based approach conceptually aligned with traditional methodologies focused on groundwater resistance through overlying sedimentary layers. Incorporating elements of groundwater recharge, travel time to the uppermost used aquifer, pollution risk and groundwater use, the enhanced aquifer vulnerability index (AVI) method revealed spatial variability in vulnerability at local and regional scales within the county. Increased aquifer vulnerability was evident within the Cedar River floodplain and other minor floodplain areas where there is greater recharge, shorter vertical groundwater travel times, the presence of point and nonpoint pollution sources, and increased water use. In upland regions underlain by unoxidized till, bedrock aquifers are largely protected from pollution, whereas in areas where the bedrock surface is relatively shallow, the protection of unoxidized till is missing and aquifer vulnerability to contamination is higher. Groundwater use reflected by incorporating 10-year capture zones into the index model identified zones where water supply aquifers are at greater risk from point and nonpoint source contamination. Overall, the new methodology adapts and greatly expands on the traditional AVI approach and can be adopted in other regions as applicable. Users are able to modify and adapt the index-based groundwater vulnerability schemes to better account for localized patterns and location-specific use and pollution risks.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Hydrogeology and Groundwater Flow in a Hummocky Prairie Pothole Complex, Northern Iowa - Keith E. Schilling; Matthew T. Streeter; Phil Kerr; Calvin F. Wolter; Elliot Anderson; Alejandro Gomez; Antonio Arenas-Amado (Wetlands, 2025)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

Evaluating the spatial patterns of U.S. urban NOx emissions using TROPOMI NO2 - Daniel L. Goldberg; Madankui Tao; Gaige Hunter Kerr; Siqi Ma; Daniel Q. Tong; Arlene M. Fiore; Angela F. Dickens; Zachariah E. Adelman; Susan C. Anenberg (Remote Sensing of Environment, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Spatiotemporal variability of dissolved inorganic macronutrients along the northern Antarctic Peninsula (1996–2019) - Thiago Monteiro; Sian F. Henley; Ricardo César Gonçalves Pollery; Carlos Rafael Borges Mendes; Mauricio Mata; Virginia Maria Tavano; Carlos Alberto Eiras Garcia; Rodrigo Kerr (Limnology and Oceanography, 2023)
The northern Antarctic Peninsula is a key region of the Southern Ocean due to its complex ocean dynamics, distinct water mass sources, and the climate‐driven changes taking place in the region. Despite the importance of macronutrients in supporting strong biological carbon uptake and storage, little is known about their spatiotemporal variability along the northern Antarctic Peninsula. Hence, we explored for the first time a 24‐year time series (1996–2019) in this region to understand the processes involved in the spatial and interannual variability of macronutrients. We found high macronutrient concentrations, even in surface waters and during strong phytoplankton blooms. Minimum concentrations of dissolved inorganic nitrogen (DIN; 16 μ mol kg −1 ), phosphate (0.7 μ mol kg −1 ), and silicic acid (40 μ mol kg −1 ) in surface waters are higher than those recorded in surrounding regions. The main source of macronutrients is the intrusions of Circumpolar Deep Water and its modified variety, while local sources (organic matter remineralization, water mass mixing, and mesoscale structures) can enhance their spatiotemporal variability. However, we identified a depletion in silicic acid due to the influence of Dense Shelf Water from the Weddell Sea. Macronutrient concentrations show substantial interannual variability driven by the balance between the intrusions of modified Circumpolar Deep Water and advection of Dense Shelf Water, which is largely modulated by the Southern Annular Mode (SAM) and to some extent by El Niño‐Southern Oscillation (ENSO). These findings are critical to improving our understanding of the natural variability of this Southern Ocean ecosystem and how it is responding to climate changes.

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Comparative analysis of pulmonary immunopathology in COVID-19 patients and experimentally SARS-CoV-2 infected hamsters - V. Herder; G. Meehan; J. Allan; G. Ilia; X. Huang; K. Kerr; J. Da Silva Filho; M. Gibbins; C. Moxon; C. Attipa; F. Trindade Maranhão Costa; M. Freire Santana; et al. (Journal of Comparative Pathology, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Long‐term, low incidence of web‐decorating by spiders in the Mariana Islands, Micronesia - Alexander M. Kerr; Joanne D. Sablan; Michelle K. Williams; Ferdinand Galsim; Philip C. Guerrero; Abram L. Townsend; J. Kawika Davis; Gregorio C. Borja; Ryszard Z. Oleksy; John F. Furey; David L. Benavente; Erin M. Derrington; et al. (Ecology, 2021)

Corrigendum: On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)

On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)
Terrestrial runoff can negatively impact marine ecosystems through stressors including excess nutrients, freshwater, sediments, and contaminants. Severe storms, which are increasing with global climate change, generate massive inputs of runoff over short timescales (hours to days); such runoff impacted offshore reefs in the northwest Gulf of Mexico (NW GoM) following severe storms in 2016 and 2017. Several weeks after coastal flooding from these events, NW GoM reef corals, sponges, and other benthic invertebrates ∼185 km offshore experienced mortality (2016 only) and/or sub-lethal stress (both years). To assess the impact of storm-derived runoff on reef filter feeders, we characterized the bacterial communities of two sponges, Agelas clathrodes and Xestospongia muta , from offshore reefs during periods of sub-lethal stress and no stress over a three-year period (2016—2018). Sponge-associated and seawater-associated bacterial communities were altered during both flood years. Additionally, we found evidence of wastewater contamination (based on 16S rRNA gene libraries and quantitative PCR) in offshore sponge samples, but not in seawater samples, following these flood years. Signs of wastewater contamination were absent during the no-flood year. We show that flood events from severe storms have the capacity to reach offshore reef ecosystems and impact resident benthic organisms. Such impacts are most readily detected if baseline data on organismal physiology and associated microbiome composition are available. This highlights the need for molecular and microbial time series of benthic organisms in near- and offshore reef ecosystems, and the continued mitigation of stormwater runoff and climate change impacts.

Changing Biogeochemistry of the Southern Ocean and Its Ecosystem Implications - Sian F. Henley; Emma L. Cavan; Sarah E. Fawcett; Rodrigo Kerr; Thiago Monteiro; Robert M. Sherrell; Andrew R. Bowie; Philip W. Boyd; David K. A. Barnes; Irene R. Schloss; Tanya Marshall; Raquel Flynn; et al. (Frontiers in Marine Science, 2020)

Quantifying the thermal tolerance of wood borers and bark beetles for the development of Joule heating as a novel phytosanitary treatment of pine logs - S. M. Pawson; M. K.-F. Bader; E. G. Brockerhoff; W. J. B. Heffernan; J. L. Kerr; B. O’Connor (Journal of Pest Science, 2019)

Olfactory Cues, Visual Cues, and Semiochemical Diversity Interact During Host Location by Invasive Forest Beetles - Jessica L. Kerr; Dave Kelly; Martin K.-F. Bader; Eckehard G. Brockerhoff (Journal of Chemical Ecology, 2017)

Using bomb radiocarbon to estimate age and growth of the white shark, Carcharodon carcharias, from the southwestern Indian Ocean - Heather M. Christiansen; Steven E. Campana; Aaron T. Fisk; Geremy Cliff; Sabine P. Wintner; Sheldon F. J. Dudley; Lisa A. Kerr; Nigel E. Hussey (Marine Biology, 2016)

An Overview of the Regional Experiments for Land-atmosphere Exchanges 2012 (REFLEX 2012) Campaign - Wim J. Timmermans; Christiaan van der Tol; Joris Timmermans; Murat Ucer; Xuelong Chen; Luis Alonso; Jose Moreno; Arnaud Carrara; Ramon Lopez; Fernando de la Cruz Tercero; Horacio L. Corcoles; Eduardo de Miguel; et al. (Acta Geophysica, 2015)

Remote Sensing of Water Resources in Semi-Arid Mediterranean Areas: the joint international laboratory TREMA - L. Jarlan; S. Khabba; S. Er-Raki; M. Le Page; L. Hanich; Y. Fakir; O. Merlin; S. Mangiarotti; S. Gascoin; J. Ezzahar; M.H. Kharrou; B. Berjamy; et al. (International Journal of Remote Sensing, 2015)

Association mapping for wood quality and growth traits in Eucalyptus globulus ssp. globulus Labill identifies nine stable marker-trait associations for seven traits - Saravanan Thavamanikumar; Luke J. McManus; Peter K. Ades; Gerd Bossinger; Desmond J. Stackpole; Richard Kerr; Sara Hadjigol; Jules S. Freeman; René E. Vaillancourt; Peng Zhu; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2014)

Deliberate Fingolimod Overdose Presenting with Delayed Hypotension and Bradycardia Responsive to Atropine - M. Stephenson; A. Wong; J. A. Rotella; N. Crump; F. Kerr; S. L. Greene (Journal of Medical Toxicology, 2014)

Derivation of Man-1 and Man-2 research grade human embryonic stem cell lines - Maria V. Camarasa; Robbie W. Kerr; Sharon F. Sneddon; Nicola Bates; Lisa Shaw; Rachel A. Oldershaw; Fiona Small; Melissa A. Baxter; Tristan R. Mckay; Daniel R. Brison; Susan J. Kimber (In Vitro Cellular & Developmental Biology - Animal, 2010)

Simultaneous freeze tolerance and avoidance in individual fungus gnats, Exechia nugatoria - Todd Sformo; F. Kohl; J. McIntyre; P. Kerr; J. G. Duman; B. M. Barnes (Journal of Comparative Physiology B, 2009)

Effect of a 20-day ski trek on fuel selection during prolonged exercise at low workload with ingestion of 13C-glucose - F. Péronnet; M. Abdelaoui; C. Lavoie; C. Marrao; S. Kerr; D. Massicotte; G. Giesbrecht (European Journal of Applied Physiology, 2009)

Spatial species‐richness gradients across scales: a meta‐analysis - Richard Field; Bradford A. Hawkins; Howard V. Cornell; David J. Currie; J. Alexandre F. Diniz‐Filho; Jean‐François Guégan; Dawn M. Kaufman; Jeremy T. Kerr; Gary G. Mittelbach; Thierry Oberdorff; Eileen M. O’Brien; John R. G. Turner (Journal of Biogeography, 2009)
Aim We surveyed the empirical literature to determine how well six diversity hypotheses account for spatial patterns in species richness across varying scales of grain and extent. Location Worldwide. Methods We identified 393 analyses (‘cases’) in 297 publications meeting our criteria. These criteria included the requirement that more than one diversity hypothesis was tested for its relationship with species richness. We grouped variables representing the hypotheses into the following ‘correlate types’: climate/productivity, environmental heterogeneity, edaphics/nutrients, area, biotic interactions and dispersal/history (colonization limitation or other historical or evolutionary effect). For each case we determined the ‘primary’ variable: the one most strongly correlated with taxon richness. We defined ‘primacy’ as the proportion of cases in which each correlate type was represented by the primary variable, relative to the number of times it was studied. We tested for differences in both primacy and mean coefficient of determination of the primary variable between the hypotheses and between categories of five grouping variables: grain, extent, taxon (animal vs. plant), habitat medium (land vs. water) and insularity (insular vs. connected). Results Climate/productivity had the highest overall primacy, and environmental heterogeneity and dispersal/history had the lowest. Primacy of climate/productivity was much higher in large‐grain and large‐extent studies than at smaller scales. It was also higher on land than in water, and much higher in connected systems than in insular ones. For other hypotheses, differences were less pronounced. Throughout, studies on plants and animals showed similar patterns. Coefficients of determination of the primary variables differed little between hypotheses and across the grouping variables, the strongest effects being low means in the smallest grain class and for edaphics/nutrients variables, and a higher mean for water than for land in connected systems but vice versa in insular systems. We highlight areas of data deficiency. Main conclusions Our results support the notion that climate and productivity play an important role in determining species richness at large scales, particularly for non‐insular, terrestrial habitats. At smaller extents and grain sizes, the primacy of the different types of correlates appears to differ little from null expectation. In our analysis, dispersal/history is rarely the best correlate of species richness, but this may reflect the difficulty of incorporating historical factors into regression models, and the collinearity between past and current climates. Our findings are consistent with the view that climate determines the capacity for species richness. However, its influence is less evident at smaller spatial scales, probably because (1) studies small in extent tend to sample little climatic range, and (2) at large grains some other influences on richness tend to vary mainly within the sampling unit.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

1,25-dihydroxyvitamin D3 protects human pancreatic islets against cytokine-induced apoptosis via down-regulation of the fas receptor - R. Riachy; B. Vandewalle; E. Moerman; S. Belaich; B. Lukowiak; V. Gmyr; G. Muharram; J. Kerr Conte; F. Pattou (Apoptosis, 2006)

Differential regulation of caspase-3 by pharmacological and developmental stimuli as demonstrated using humanised caspase-3 mice - L. E. Kerr; J-L. A. Birse-Archbold; A. Simon; N. Logan; F. Scott; G. Carlson; D. W. Nicholson; J. S. Kelly; J. Sharkey (Apoptosis, 2004)

Factors enhancing lycopene production by a new Mycobacterium aurum mutant - S. Kerr; C. Calé; J.M.S. Cabral; F. van Keulen (Biotechnology Letters, 2004)

Definition of the domain boundaries is critical to the expression of the nucleotide-binding domains of P-glycoprotein - Ian D. Kerr; Georgina Berridge; Kenneth J. Linton; Christopher F. Higgins; Richard Callaghan (European Biophysics Journal, 2003)

Slant Column Measurements of O3 and NO2 During the NDSC Intercomparison of Zenith-Sky UV-Visible Spectrometers in June 1996 - H. K. Roscoe; P. V. Johnston; M. Van Roozendael; A. Richter; A. Sarkissian; J. Roscoe; K. E. Preston; J-C. Lambert; C. Hermans; W. DeCuyper; S. Dzienus; T. Winterrath; et al. (Journal of Atmospheric Chemistry, 1999)